2015
DOI: 10.4049/jimmunol.1501353
|View full text |Cite
|
Sign up to set email alerts
|

Stat1 Regulates Lupus-like Chronic Graft-versus-Host Disease Severity via Interactions with Stat3

Abstract: Systemic lupus erythematosus (SLE) is a complex multisystem autoimmune disease, characterized by a spectrum of autoantibodies that target multiple cellular components. Glomerulonephritis is a major cause of morbidity in patients with SLE. Little is known about the pathogenesis of SLE renal damage and compromised renal function. Activation of both Stat1 and Stat3 has been reported in lupus and lupus nephritis. The reciprocal activation of these two transcription factors may have a major impact on renal inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 39 publications
3
18
0
Order By: Relevance
“…Stat3 activation was associated with SOCS3 down regulation in the kidneys of the same mice. Consistent with previous findings, data shown here suggest a negative regulatory role for SOCS3 on Stat3 activation (35, 36). In addition, our previous data showed that Stat3 activation in the kidney was associated with severe nephritis in chronic graft-versus-host disease (cGVHD) (35).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Stat3 activation was associated with SOCS3 down regulation in the kidneys of the same mice. Consistent with previous findings, data shown here suggest a negative regulatory role for SOCS3 on Stat3 activation (35, 36). In addition, our previous data showed that Stat3 activation in the kidney was associated with severe nephritis in chronic graft-versus-host disease (cGVHD) (35).…”
Section: Resultssupporting
confidence: 93%
“…An additional consequence of caspase1 activation in macrophages is rapid and caspase-1-dependent cell death (43). Increased IL-1 secretion and enhanced apoptotic cell death were reported previously in the kidneys of Mer-KO mice injected with NTS (35). Strikingly, Caspase1 activation (cleavage) was only observed in the kidneys of the nephritic mice lacking the Mer receptor, indicating a Mer-dependent caspase1 inhibition.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…To study the role of Stat1 in a lupus model, we induced SLE-like chronic graft-versus-host disease (cGVHD) in Stat1-KO and in WT mice by intraperitoneal injection of class II-disparate bm12 splenocytes [6]. WT recipients of these alloreactive cells developed anti-dsDNA autoantibodies starting at week 2 as expected, with a decline after week 4.…”
Section: Introductionmentioning
confidence: 94%
“…Enhanced expression and activation of Stat3 were observed in the glomeruli of Stat1-KO host mice but not WT mice with cGVHD. Interactions between Stat1 and Stat3 thus appear to be crucial in determining the severity of lupus-like disease in the cGVHD model [6].…”
Section: Introductionmentioning
confidence: 99%